The Effect of Teacher’s Professional and Social Competency on Student’s Learning Outcomes - Maryani, Sri; Lian, Bukman; Rohana, Rohana (Yayasan Sembilan Pemuda Indonesia, 2021)
The teacher determines the success of students because of the teacher's strategic position as a guide in learning. In order for a teacher's job to work well, the teacher must be professional in teaching. Professional teachers are believed to be able to make students think, behave and act creatively. This quantitative study aims to measure the effect of professional and social competence of teachers on learning outcomes of elementary school students in the Gelumbang District of Muara Enim Regency, which were analyzed using multiple regression formulas and supported by SPSS For Windows Version 21, data collection techniques including questionnaires, documentation in the form of photographs related to research. The results obtained that the of influence of professional and social competence together contribute to the learning outcomes of elementary school students in Gelumbang District. This paper is different from previous studies, it provides the new paradigm to focus on profesional and social competence where we could have good learning outcomes of student.